Modernization and Devolution: Delivering Services for Older People in Rural Areas of England and Wales. (10th October 2012) - Doheny, Shane; Milbourne, Paul
Abstract: The modernization of public services, with its emphasis on managerialism, choice, co‐production and outcome focused service delivery, has been implemented to a certain extent in both England and Wales. Indeed, the welfare states in both countries share a great deal, particularly in relation to policy objectives and the expectations of citizens. Devolution has chiefly meant that the instruments used to deliver policy have separated, although it remains unclear whether this amounts to formal divergence. What is also unclear is to what extent have the experiences of those living within the policy environment in both countries separated or diverged? This article addresses this question using qualitative data composed of interviews with policy actors in six rural areas of England and Wales. By focusing on the discourses of people involved in modernizing and providing services for older people in rural areas, we bring out the impact of modernization for older people. What we show is that modernization engages both service users and the wider population who may one day become service users. But the emphasis on these groups unfolds in different ways in England and Wales. In England, where there has been a commitment to a customer citizen, policy at the local level has emphasized re‐enablement, community development and individual responsibility. In Wales, where modernization has focused on collaboration and citizenship, local policies have focused on service users, and on engagement with the voluntary sector. In effect, the policy environment provides a different context for the experience of ageing in both countries.